Informality and Bank Credit : Evidence from Firm-Level Data - Koeda, Junko (IMF Working Papers; Working Paper, 2008)
The paper relies on a firm-level data on transition economies to examine the relationship between informality and bank credit. We find evidence that informality is robustly and significantly associated with lower access to and use of bank credit. We also find that higher tax compliance costs reduce firms' reliance on bank credit, while a stronger quality of the legal environment is associated with higher access to credit even for financially opaque informal firms. An interactive term between a country-wide measure of tax compliance costs and the level of informal activity is negative and significant, suggesting that the negative association between informality and bank credit is stronger in countries with weak tax administration.